2003
DOI: 10.1002/iroh.200390000
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the Heavy Metal Cycle to Industrial Activities in the Deep Sea: An Ecological Assessment

Abstract: This article focuses on possible geochemical consequences of potential industrial activities in the deep sea, such as manganese nodule mining, for the heavy metal cycle of the deep sea and possible reactions of the benthic ecosystem. The metal fluxes induced by sediment resuspension are compared with fluvial, atmospheric, and hydrothermal metal fluxes into the ocean. The results of geochemical laboratory experiments and analyses of deep-sea benthic organisms are discussed with respect to their ecological impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…Studies on metal accumulation in fish are often hampered by the lack of certainty about their history and exposure rates (e.g., Brewer et al, 2007 (Koschinsky et al, 2003).…”
Section: Bioaccumulation/ Bioconcentration/ Biomagnificationmentioning
confidence: 99%
“…Studies on metal accumulation in fish are often hampered by the lack of certainty about their history and exposure rates (e.g., Brewer et al, 2007 (Koschinsky et al, 2003).…”
Section: Bioaccumulation/ Bioconcentration/ Biomagnificationmentioning
confidence: 99%
“…[26] and [27] reported that a single biomarker cannot provide the basic answers as to what is the actual state of health in the natural populations and that, environmental stress may cause changes in cellular function that alter the physiology of organ system in organisms, suggesting that pollutants might influence the metabolism of the whole organism. [28] and [29] discovered a relationship between xenobiotic chemicals accumulated in oyster (Crassostrea virginica) tissue and various measures of physiological condition and that the possibility of variations of metals concentration due to physiological parameters have been taken into consideration such as stress. In the present study, variations of metal concentrations are to be attributed to variation of metal concentrations in the surrounding water.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, the only published records of metal concentrations in deep-sea amphipods are those from benthopelagic amphipods, putatively identified as E. gryllus, collected from the Peru Basin Mn nodule field (Koschinsky et al, 2003). This highlights the paucity of information on regional variation in metal concentrations in deep-sea habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Within open ocean pelagic and deep-sea habitats, metals can be released into the water via remineralisation of faecal pellets, fluids from hydrothermal vent systems, weathering of mineral deposits, sedimentary diagenic recycling of metals and the input of aeolian material (e.g. dust) which binds to POM that subsequently sinks (Bennett et al, 2008;Chu et al, 2006;German et al, 2010;Grand et al, 2015;Hauton et al, 2017;Koschinsky et al, 2003;Laglera et al, 2017;Ratnarajah et al, 2014;Yucel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%